Evaluation of the relationships among happiness, stress, anxiety, and depression in pharmacy students - Silva, Rute Gonçalves; Figueiredo-Braga, Margarida (Currents in pharmacy teaching and learning, 2018)
To present the results of a survey on stress, anxiety, depression, subjective happiness, and academic satisfaction among pharmacy students. A total of 410 pharmacy students, were included. Sociodemographic characteristics, stress, anxiety and depressive symptoms, and happiness were evaluated using the Perceived Stress Scale (PSS), Hospital Anxiety and Depression Scale (HADS), and Subjective Happiness Scale (SHS), in May 2015. First and second year student's (n = 200) presented higher levels of academic satisfaction (p = 0.003) and lower levels of stress (p < 0.001), anxiety (p = 0.011) and depression (p = 0.010) than third and fourth year students (n = 210). Academic satisfaction, HADS, and the PSS explained 36.7% of the students’ happiness. The student's psychological distress, academic satisfaction, and happiness varies through the school years. Monitoring a probable cumulative effect during pharmacy school may contribute to identify students at risk.